2012
DOI: 10.1007/s00726-012-1246-6
|View full text |Cite
|
Sign up to set email alerts
|

Creatine-induced glucose uptake in type 2 diabetes: a role for AMPK-α?

Abstract: This study focused on understanding the signaling mechanisms leading to GLUT-4 translocation and increased skeletal-muscle glucose uptake that follow creatine (Cr) supplementation in type 2 diabetes (n = 10). AMPK-α protein content presented a tendency to be higher (p = 0.06) after Cr supplementation (5 g/d for 12w). The changes in AMPK-α protein content significantly related (p < 0.001) to the changes in GLUT-4 translocation (r = 0.78) and Hb1Ac levels (r = -0.68), suggesting that AMPK signaling may be implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
1
22
0
3
Order By: Relevance
“…Another proposed mechanism discussed for increasing muscle mass is the concentration of intracellular water, responsible to enhance the cell hydration state. This effect may be related to increase protein synthesis, besides increases the expression of myogenic transcription factors (26,28,39,40). However, the mechanisms by which creatine exerts beneficial effects in the immobilization are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed mechanism discussed for increasing muscle mass is the concentration of intracellular water, responsible to enhance the cell hydration state. This effect may be related to increase protein synthesis, besides increases the expression of myogenic transcription factors (26,28,39,40). However, the mechanisms by which creatine exerts beneficial effects in the immobilization are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that creatine use has an effect similar to that of sulfonylurea in glycemic control in type 2 diabetic patients (Rocic et al, 1999) and that using creatine may lead to similar results as observed in patients treated with metformin (Bajuk et al, 2001). According to the results Alves et al (2012), this effect of creatine supplementation may be explained by the significant relationship between the increased expression of protein kinase alpha (AMPK-?) and the decreased level of glycated hemoglobin (Hb1Ac), with a consequent increase in the translocation of glucose transporter 4 (GLUT-4).…”
Section: Glucose Uptakementioning
confidence: 97%
“…Two double-blind, randomized placebo-controlled trials examined the effects of creatine in patients diagnosed with T2DM Alves et al 2012). In both studies, creatine and placebo groups underwent a moderate intensity aerobic training combined with strengthening exercises.…”
Section: Human Studiesmentioning
confidence: 99%
“…Six studies (Op't Eijnde et al 2001;Newman et al 2003;Derave et al 2003;Van Loon et al 2004;Safdar et al 2008;Gualano et al 2008) used a creatine supplementation loading phase followed by a maintenance phase, and two studies maintained the same low dosage for the entire experiment Alves et al 2012). Five trials tested only creatine (Op't Eijnde et al 2001;Safdar et al 2008;Gualano et al 2008Gualano et al , 2011Alves et al 2012), 2 trials tested creatine plus glucose Van Loon et al 2004), and 1 creatine and/or protein and amino acids . Some trials included moderate intensity aerobic training combined with strengthening exercises Alves et al 2012) or a rehabilitation program after immobilization (Op't Eijnde et al 2001;Derave et al 2003).…”
mentioning
confidence: 98%
See 1 more Smart Citation